Fine needle aspiration cytologic and histologic correlation in canine mammary tumors - Zuccari, Debora Aparecida Pires de Campos; Santana, Aureo Evangelista; Rocha, Noeme Souza (Brazilian Journal of Veterinary Research and Animal Science, 2001)
Cytologic and histologic examination of 35 canine mammary masses was performed over a year period, from dogs that underwent mastectomy for mammary neoplasms at the UNESP Veterinary Medical Teaching Hospital -- Jaboticabal (SP) Brazil. The mastectomy specimens were evaluated according to structural parameters found to be prognostically significant in human mammary tumors, such as grade of atypia, nuclear criteria (shape, size, form, abnormal mitotic figures), chromatin and nucleolar patterns, high cellularity and poor intercellular cohesions. These criteria were used for differentiation of benign from malignant mammary tumors with 63% of a concordant diagnosis and sensibility of 73% and specificity of 83%. The "fine needle aspiration" technique is discussed as a tool to perform early diagnosis. Our data were found to have a positive correlation to the prognosis indicating that we can recognize structural variables of malignancy by citopathology. Application of the described parameters should facilitate comparative studies of histopathologic diagnosis with biologic behavior of canine mammary tumors using this technique to obtain early diagnosis and a secure prognosis.